“Experimental Оncology” is the best scientific journal In Ukraine according To scopus! (Experimental Oncology, 2016)
International scientific journal “Experimental Оncology” (Publishing House “MORION LLC”, Kyiv, Ukraine — R.E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology of the NAS of Ukraine, Kyiv, Ukraine) earned high global recognition, receiving the prestigious international award “SCOPUS Awards Ukraine” as a winner in the category “The Best Journal”.